Association Between Respiratory Syncytial Virus-Associated Acute Lower Respiratory Infection in Early Life and Recurrent Wheeze and Asthma in Later Childhood. (1st August 2019) - Shi, Ting; Ooi, Yujing; Zaw, Ei Mon; Utjesanovic, Natasa; Campbell, Harry; Cunningham, Steve; Bont, Louis; Nair, Harish; ,
Abstract: Background: Recurrent wheeze and asthma in childhood are commons causes of chronic respiratory morbidity globally. We aimed to explore the association between respiratory syncytial virus (RSV) infection in early life and subsequent respiratory sequelae up to age 12 years. Methods: We estimated the strength of association by 3 control groups and 3 follow-up age groups, with data from studies published between January 1995 and May 2018. We also estimated associations by diagnostic criteria, age at infection, and high-risk population. Results: Overall, we included 41 studies. A statistically significant association was observed between early life RSV infection and subsequent childhood recurrent wheeze, in comparison to those who were healthy or those without respiratory symptoms: OR 3.05 (95% confidence interval [CI], 2.50–3.71) for 0 to <36 months follow-up age; OR 2.60 (95% CI, 1.67–4.04) for 36–72 months; and OR 2.14 (95% CI, 1.33–3.45) for 73–144 months. For the subsequent development of asthma, a statistically significant association was observed only in relation to those aged 73–144 months at follow-up: OR 2.95 (95% CI, 1.96–4.46). Conclusions: Further studies using standardized definitions and from diverse settings are needed to elucidate the role of confounders and provide more robust estimates.